STABILITY-INDICATING HIGH-PERFORMANCE THIN-LAYER CHROMATOGRAPHY METHOD FOR SIMULTANEOUS ESTIMATION OF FORMOTEROL FUMARATE DIHYDRATE AND FLUTICASONE PROPIONATE IN BULK DRUG AND PHARMACEUTICAL DOSAGE FORM - RAJASHI B PHARATE,; SUNEELA S DHANESHWAR, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present work was to develop validated stability-indicating high-performance thin-layer chromatographic method for simultaneous estimation of formoterol fumarate dihydrate (FFD) and fluticasone propionate (FP) in bulk drug and pharmaceutical dosage form. Methods: Pre-coated silica gel aluminum plates 60 F-254 were used as stationary phase. The mixture of toluene:ethyl acetate:formic acid (98%) (6:4:0.1; v/v/v) was used as a mobile phase. The densitometric quantification was carried out at 233 nm. The method was validated according to the ICH guidelines. The specificity and stability indicating the capability of the method were proven though degradation studies. Both drugs were subjected to acid (0.1N HCl) and base (0.1N NaOH) hydrolysis, oxidation (3% v/v H2O2), photolytic, and neutral degradation conditions. Results: The selected mobile phase resolved peaks of FFD and FP with Rf values 0.27±0.10 and 0.64±0.10, respectively. Determination coefficients of calibration curves were found to be 0.998 and 0.999 in the range of 1–3.5 μg/spot and 10–60 μg/spot for FFD and FP with an accuracy of 99.09% for FFD and 99.20% for FP. The degradation products of FFD and FP were resolved from the pure drug with significant differences in their retention factor values. Conclusion: The developed method is simple, accurate and can be successfully applied for quantification of FFD and FP in bulk drug and pharmaceutical dosage form, contributing to improve the quality control and assure the therapeutic efficacy.